‘What are people for?’ - Yat Shun Kei (Footprint)
This article revisits previously overlooked exchanges between pre-eminent figures in British architecture and ecology, William Holford, Julian Huxley, and Max Nicholson, which were incorporated in one of the earliest uses of the term ‘built environment’ in 1964. By examining how an energy-entropy interpretation of the ecosystem had shaped their views on the natural, human-made, and psychosocial milieu, I will consider the way cybernetics conditioned the articulation of the built environment. Contextualising their exchanges in the socio-cultural climate of the early 1960s, I trace an almost  concurrent environmental turn made by architecture and ecology. Moreover,  the exchange between architecture and ecology has engendered an environmental conception that prioritised the transformative and reciprocal relationship between humans and what surrounds them. In this effort, I pay particular attention to a co-evolutionary view of the technosphere, biosphere, and political sphere formulated by Nicholson. I also discuss the infiltration of eugenic and technocratic views in this reconceptualisation of the environment. Despite the peculiarities of these theories, their conceptualisation of the environment had pointed towards an important question in employing the ecosystemic metaphor: what are people for?